Lexicon of grammatical-semantic features: discontinuity - Vondráček, Miloslav (Bohemistyka, 2023)
The contribution represents a fragment of an intended Lexicon of grammatical-semantic features. It presents only very general properties as components of grammatical categories and the results of their presence or non-presence for category value interpretation and for (in)compatibility of language means. Grammatical features of a lexical unit can be described with the help of the tagset, i.e., analytical morphological label. Similarly, it is possible to describe a complete grammeme on the principle of fractals, including inner structure of each grammatical category and their values with the help of sets of grammatical-semantic properties. Grammatical-semantic properties bound on lexical forms are not isolated from lexical-semantic features: the first can be considered as a result of grammaticalization of the latter. From the chosen point of view, the construction of grammar from a semantic basis seems to be as a multi-level phenomenon to such a level in which grammatical-semantic properties are based on similarity and contrast in the area of lexical-semantic properties.